2017
DOI: 10.1002/jbm.a.36051
|View full text |Cite
|
Sign up to set email alerts
|

Insulin‐like growth factor‐1 (IGF‐1) enhances the osteogenic activity of bone morphogenetic protein‐6 (BMP‐6) in vitro and in vivo, and together have a stronger osteogenic effect than when IGF‐1 is combined with BMP‐2

Abstract: Bone morphogenetic protein-2 (BMP-2) is widely used in orthopedic surgery and bone tissue engineering because of its strong osteogenic activity. However, BMP-2 treatments have several drawbacks and many groups are actively exploring alternatives. Since BMP-6 has been demonstrated to be more osteoinductive, its use, either alone or together with other growth factors, might be an interesting option. In this work, we have compared the effect of BMP-2, BMP-6, or insulin-like growth factor-1 (IGF-1), either alone o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 47 publications
0
24
0
1
Order By: Relevance
“…Some studies indicated that IGF-1 is an important growth factor that can stimulate bone regeneration by enhancing osteoblast proliferation, bone matrix synthesis, osteoblastic gene expression, ALP activity and mineralization[ 15 , 29 33 ]. However, some recent studies showed that IGF-1 alone does not improve osteogenic proliferation[ 23 ], ALP activity[ 34 ], osteogenic differentiation[ 22 ] and mineralization[ 35 ]. We speculated that IGF-1 has a dose-dependent effect on osteogenesis, and different IGF-1 doses may lead to different levels of osteoblastic proliferation or differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies indicated that IGF-1 is an important growth factor that can stimulate bone regeneration by enhancing osteoblast proliferation, bone matrix synthesis, osteoblastic gene expression, ALP activity and mineralization[ 15 , 29 33 ]. However, some recent studies showed that IGF-1 alone does not improve osteogenic proliferation[ 23 ], ALP activity[ 34 ], osteogenic differentiation[ 22 ] and mineralization[ 35 ]. We speculated that IGF-1 has a dose-dependent effect on osteogenesis, and different IGF-1 doses may lead to different levels of osteoblastic proliferation or differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, IGF‐1 in combination with BMP‐ 2 have a stimulatory effect on the proliferation and osteogenic differentiation of stem cells derived from adipose tissue (Elias, ). Another study revealed that the combination of BMP‐6 with IGF‐1 might be a better alternative than BMP‐2 for inducing bone formation and increase in mineralization in the implants in orthopedic surgery or bone tissue engineering approaches (Rico‐Llanos, Becerra, & Visser, ). Results of a randomized controlled clinical study showed that combined use of VEGF and IGF‐I in conjunction with Polylactide‐Polyglycolide Acid (PLGA) membrane and β‐Tricalcium Phosphate (β‐TCP) osseous graft resulted in enhanced clinical outcomes in terms of pocket reduction, clinical attachment Level gain and bone fill as compared to VEGF and IGF‐I used alone (Devi & Dixit, ).…”
Section: Introductionmentioning
confidence: 99%
“…When 10 pmole of BMP-2 or BMP-6 was administered, bone formation was observed in BMP-6 groups, indicating that BMP-6 may be a superior alternative than BMP-2 for inducing bone formation. 141 This is crucial as supraphysiological administration of BMP-2 has been reported to cause life-threatening cervical spine swelling. 142 PTH and PTH-related peptide (PTHrP), including their analogs, such as Teriparatide (shares the first 1-34 amino acid residues of PTH) and Abaloparatide (shares the first 1-22 amino acid residues of PTHrP), as well as humanized monoclonal antibodies, such as Romosozumab (targets Sclerostin, whose production is normally inhibited by PTH), have been widely investigated for their use in bone anabolic therapy.…”
Section: Growth Factor-based Therapymentioning
confidence: 99%